(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
The combination of two words i.e., Nutraceuticals and Cosmeceuticals. we can say combination of two words i.e., Nutrition and Cosmetics. These are the products which contain collagen, antioxidants, carotenoids, polyphenols, vitamins, omega 3 fatty acids, etc. These products or supplements are in the form of capsules, tablets, powder, or drinking vials. Normally we apply cosmetic products to our skin to enhance our beauty, but we forget that beauty comes from inside. The cosmetic products which we use to enhance our beauty only work on the upper layer of our skin. They form a layer on the outer layer of our skin. Like in market there are various cosmetic products like various types of creams such as anti -ageing cream, anti-inflammatory wrinkle cream, moisturizing creams etc., these creams form a layer on the epidermis. While Nutricosmetics works from the inside of our body. And enhance the beauty. There are various Nutricosmetics industries in India which manufacture various types of supplements which help our skin, like Nestle, Dabur, Himalaya, Ranbaxy, Amway, Lupin etc. It is a very easy and convenient solution to support beauty from within. The Indian beauty industry expanding at a very good rate. And as we know in India various types of plants or medicinal plants are found that’s why it helps a lot. Carotenoids Lycopene, Flavonoids, Polyphenols, Collagen, Vitamins, Herbs are used in the manufacturing of the products at a very good rate. And these products really help our skin to become good.